Analisis Keterampilan Teknik Dasar Passing Atas Permainan Bolavoli Siswa Ekstrakurikuler Sma Negeri 3 Luwu Utara - Wahyu Prastio Rosadi; Saman Saman; Suaib Nur (Universitas Hamzanwadi, 2025)
This study was motivated by the absence of empirical data on the basic overhead passing skills of extracurricular volleyball students at SMA Negeri 3 Luwu Utara, despite routine training sessions. The absence of systematic measurement has made it difficult for coaches to design targeted training programs. This study aims to determine the level of basic overhead passing skills in volleyball among extracurricular students at SMA Negeri 3 Luwu Utara. This research employed a survey method with a test technique using the AAHPER Face Wall-Volley Test, which measures the number of successful wall volleys using overhead passing technique within 30 seconds. The population comprised all students participating in volleyball extracurricular activities, and a saturated sampling technique was used, involving all 15 students as samples. The results showed that 12 students (80%) were in the